2016
DOI: 10.1016/j.bbmt.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors Associated with Cord Graft Failure after Transplant with Single-Unit Umbilical Cord Cells Supplemented by Haploidentical Cells with Reduced-Intensity Conditioning

Abstract: Delayed engraftment and cord graft failure (CGF) are serious complications after unrelated cord blood (UCB) hematopoietic stem cell transplantation (HSCT), particularly when using low-cell-dose UCB units. The haplo-cord HSCT approach allows the use of a lower dose single UCB unit by co-infusion of a CD34+ selected haploidentical graft, which provides early transient engraftment while awaiting durable UCB engraftment. We describe the frequency, complications, and risk factors of CGF after reduced-intensity cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…We continue efforts to enhance UCB engraftment in this setting by limiting the cell dose of the haplo-identical graft, 4;6 avoiding haplo-grafts which are matched to the recipient at more than 5 of 8 HLA-alleles, 44 by avoiding grafts targeted by donor specific antibodies and by selecting appropriate cord blood units. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We continue efforts to enhance UCB engraftment in this setting by limiting the cell dose of the haplo-identical graft, 4;6 avoiding haplo-grafts which are matched to the recipient at more than 5 of 8 HLA-alleles, 44 by avoiding grafts targeted by donor specific antibodies and by selecting appropriate cord blood units. 9 …”
Section: Discussionmentioning
confidence: 99%
“…But there are occasional cases where the cord blood graft fails and recipients are left with a permanent adult mismatched graft, or more commonly mixed chimerism. 6 In a previous report, we analyzed causes of umbilical cord graft failure. 6 Here we studied the implications of patterns of engraftment on disease recurrence in patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, 6,7,8,9 To improve the neutrophil and platelet engraftment and take advantage of the low incidence of graft-versus-host-disease (GVHD), we and others previously reported combining haploidentical donor grafts with cord blood stem cells. 1014 The haploidentical graft provides a “myeloid bridge” that allows for rapid neutrophil and platelet recovery and that –with rare exceptions 15 - is eventually replaced by the cord blood cells. We and other have previously reported on patterns of chimerism, 14, 1618 its consequences and of immune reconstitution 19, 20 after this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we found that patients who received very high CD34 doses from the haplo-identical donor had impaired/delayed umbilical cord blood engraftment. 6 More recently we have limited the cell dose of the haplo-graft to ~3 ×10 6 CD34/kg rec . But occasional cases of haplo-dominance continue to occur.…”
mentioning
confidence: 99%